Coronary Artery Disease (CAD) in young Indians: An autopsy study - Sarkar, Kumarjit; Chakrabarty, Debashis; KumarBose , Tapas (Journal of Indian Academy of Forensic Medicine, 2019)
Coronary Artery Disease (CAD) is a leading cause of death worldwide. Atherosclerosis, the cause of CAD, is emerging as the single largest disease accounting for nearly one-third of all deaths in India. A study to evaluate the Microscopic Grading of CAD in young individuals and to find its relationship with the age and sex was done for one year. Tissues of coronary artery from 55 cases of medico legal autopsy were collected and studied for Histopathology. The findings were graded as per guidelines of American Heart Association. Out of 18 patients in the age group less than 30 years, 16 (77.8%) were males and 2 (22.2%) were females. Out of 37 cases (30 –39 years), 26 were males (70.3%) and 11 females (29.7%). Out of 37cases belonging to the age group of 30-39 years, 7(18.9%) cases had type I-III changes while30(81.1%) cases had type IV-VI changes [χ (5) = 30.65 p = 0.000 (confidence interval 95%)]. According to our study, young Indians dying due to non-cardiac causes show significant positive CAD changes. This is quite high in comparison with corresponding non-Indian cohorts. Majority affected were males (40/55:72.7%) as compared to the females. The high Incidence of CAD in young people is quite alarming. The data obtained may form a baseline for the forthcoming studies of CAD, especially if done on a multi-centric basis.